Indonesian structure in style of thinking: The threat of textual rhetoric - PURWANTO, B.; MULYATI, S.; MULYONO, T.; MULJANI, S.; HANANI, N.; YASIN, M. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The general objective of this research is to discover the characteristics of Indonesian language structures in thinking styles. This study uses a descriptive approach. Random Abstract thinking style (AA) was found to be the most dominant in this study and followed by Sequential Thinking style (SK) as the second dominance. They process information in an orderly and linear manner. For this mindset student, the reality is what can be absorbed through the physical senses namely vision, contact, and pronunciation.RESUMEN El objetivo general de esta investigación es descubrir las características de las estructuras lingüísticas de Indonesia en los estilos de pensamiento. Este estudio utiliza un enfoque descriptivo. Se encontró que el estilo aleatorio de pensamiento abstracto (AA) era el más dominante en este estudio, seguido del estilo de pensamiento secuencial (SK) como el segundo dominante. Procesan la información de manera ordenada y lineal. Para la mentalidad del estudiante, la realidad es lo que se puede entender a través de los sentidos físicos, es decir, la visión.